William Shakespeare's King Lear - Bloom, Harold (New Delhi : Viva, 2007)
Includes a brief biography of the author, thematic and structural analysis of the work, critical views, and an index of themes and ideas.
Keywords: Shakespeare, William -- 1564-1616.; Lear, -- King of England (Legendary character) -- In literature; Shakespeare, William, -- 1564-1616.; Tragedy; English literature -- History and criticism